Factors affecting entrepreneurial intention: evidence from Khulna University, Bangladesh - Sraboni Akter; Saimur Rahman (Journal of Sustainable Tourism and Entrepreneurship, 2020)
Purpose: This study aimed to investigate the influence of factors affecting entrepreneurial intention and finally show the relationship between those factors on entrepreneurial intention. Research methodology: This study used explanatory and inferential methods. Data was collected using a closed-ended questionnaire. The program used was SPSS Version 16.00. Results: We found a positive and significant relationship with all the factors besides entrepreneurial education and gender differences. Limitation: The study is limited to the respondents’ bias and restriction to only one particular university. Contribution: This study’s results contribute to understanding the importance of entrepreneurial education to the university and arranging more seminars and case study and introducing some inspired entrepreneurs for the student’s betterment. Keywords: Autonomy, Entrepreneurial education, Entrepreneurial intention, Need for achievement, Locus of control